PENGARUH FAKTOR PENDAPATAN, UMUR, JUMLAH TANGGUNGAN KELUARGA, PENDAPATAN SUAMI DAN JARAK TEMPUH KE TEMPAT KERJA TERHADAP CURAHAN JAM KERJA PEDAGANG SAYUR WANITA (Studi kasus di Pasar Umum Purwodadi) - Nanda Ayu Kusumastuti; Evi Yulia Purwanti (Diponegoro Journal of Economics, 2012)
ABSTRACT This studies aims to analyze the factors which influence the hours of work for the female vegetable traders with The Market in Purwodadi City. The factors are including income, age, number of dependents, husband’s revenue, mileage to market; and finding out the contribution of female vegetable traders’ income to total household income. This studies was conducted in The Market of Purwodadi City, by drawing a sample of 82 from a population of 104. The sample was drawn by random sampling method. The analytical tool used in the study is multiple linier regression or Ordinary Least Square (OLS) with the hours of work female vegetable  traders into the dependent variable and five independent variables are income, age, number of dependents, husband’s revenue, mileage to market. The method of doing his study is interview with questioner (direct interview) The result of analysis showed that income, number of dependents and mileage to market influenced positively and significant to the hours of work. The age and the husband’s revenue showed that there was no significant and influenced negatively to hours of work. The total income of female vegetable traders was contributed to household income, and as a whole, the contribution of female vegetable traders to total household income was 44,01 percent.